Adherence to combined Antiretroviral therapy (cART) among people living with HIV/AIDS in a Tertiary Hospital in Ilorin, Nigeria - Anyaike, Chukwuma (Pan Afr Med J, 2019)
INTRODUCTION: This study aims to assess the treatment adherence rate among People Living With HIV/AIDS (PLWHA) receiving treatment in a Nigerian tertiary Hospital. METHODS: This was a cross-sectional study that assessed self-reported treatment adherence among adults aged 18 years and above who were accessing drugs for the treatment of HIV. Systematic random sampling method was used to select 550 participants and data were collected by structured interviewer administered questionnaire. RESULTS: The mean age of respondents was 39.9±10 years. Adherence rate for HIV patients was 92.6%. Factors affecting adherence include lack of money for transportation to the hospital (75%), traveling (68.8%), forgetting (66.7%), avoiding side effects (66.7%), and avoiding being seen (63.6%). CONCLUSION: The adherence rate was less than optimal despite advancements in treatment programmes. Adherence monitoring plans such as home visit and care should be sustained.